DILEMATIKA PELAKSANAAN OTONOMI DI BIDANG PENGELOLAAN SUMBERDAYA ALAM/AGRARIA - Sarjita, Sarjita (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
The management of natural/agrarian resources in the reformation era influence the governance of the government after Amendment of the 1945 Constitution. The article is aimed at analyzing the crusial problems related to the right of the central government on managing (the land, forestry, mining, and taxation) problems. Yet, at present, those duties are implemented by the provincial and regional governments. The result of the analysis showed that the implementation caused the decrease of the environmental quality, overlapping of services and so forth. Therefore, to make the regulations accord with the constitution, the break law by the judges of the constitutional court was badly required. Keywords: dilemma, implementation, management natural/agrarian resources.